2014
DOI: 10.1038/srep04348
|View full text |Cite
|
Sign up to set email alerts
|

The plasma protein fibrinogen stabilizes clusters of red blood cells in microcapillary flows

Abstract: The supply of oxygen and nutrients and the disposal of metabolic waste in the organs depend strongly on how blood, especially red blood cells, flow through the microvascular network. Macromolecular plasma proteins such as fibrinogen cause red blood cells to form large aggregates, called rouleaux, which are usually assumed to be disaggregated in the circulation due to the shear forces present in bulk flow. This leads to the assumption that rouleaux formation is only relevant in the venule network and in arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
127
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 31 publications
9
127
1
Order By: Relevance
“…This might be a limitation of the flow-chamber experiments, as in the latest work using an AFM, it was shown that RBCs do interact with each other in a solution of fibrinogen alone. 19 A monotonic increase in interaction energy along with an increase in fibrinogen concentration was observed. The interaction between RBCs in a fibrinogen solution (4 mg∕ml) was also qualitatively observed by Bronkhorst et al 23 using OT.…”
Section: Fibrinogen-induced Red Blood Cell Aggregationmentioning
confidence: 91%
See 2 more Smart Citations
“…This might be a limitation of the flow-chamber experiments, as in the latest work using an AFM, it was shown that RBCs do interact with each other in a solution of fibrinogen alone. 19 A monotonic increase in interaction energy along with an increase in fibrinogen concentration was observed. The interaction between RBCs in a fibrinogen solution (4 mg∕ml) was also qualitatively observed by Bronkhorst et al 23 using OT.…”
Section: Fibrinogen-induced Red Blood Cell Aggregationmentioning
confidence: 91%
“…19,23,32 Our results give more specific information that most likely fibrinogen is the protein responsible for the disaggregation kinetics of RBCs, while for spontaneous aggregation, it has no effect when present alone or only with albumin in the solution. It was shown by the disaggregation force measurements that RBC interaction is strong even if fibrinogen is the sole protein in the solution.…”
Section: Fibrinogen-induced Red Blood Cell Aggregationmentioning
confidence: 92%
See 1 more Smart Citation
“…1). The physical origin of this cluster formation can be either the long-ranged hydrodynamic interaction [2][3][4][5][6] or a short-range aggregation mechanism, which is caused by the plasma macromolecules 7 . The latter relates to the so-called rouleaux formation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In former studies on cluster formation, either no macromolecules were added and only hydrodynamic effects were present 6 , or the effects of the macromolecules were tested in channels that were smaller than the RBC diameter with the effect of hydrodynamic attraction minimized 7 . In this study, we allow both mechanisms to take effect and we observe that both are relevant, but they form clusters of notably different geometrical forms.…”
Section: Introductionmentioning
confidence: 99%